Meet the Expert Kip Harkness and Tim O'Reilly on Turning Your City's COVID-19 Response into an Agile Action Plan - Harkness, Kip; O'Reilly, Tim (O'Reilly Media, Inc., 2020)
The city of San Jose, located in the heart of Santa Clara County, is one of the areas of California hardest hit by the COVID-19 epidemic. In mid-March 2020, Kip Harkness, San Jose's deputy city manager, led the effort to get the city's leadership team all on the same page about its COVID-19 emergency action plan. In this Meet the Expert session, Kip talks with Tim O'Reilly about the process San Jose used to build its road map to realign its priorities around response to the emergency. See how San Jose used Agile methods such as Weighted Shortest Job First prioritization to develop its disaster response procedures and learn how the resulting road map was translated into one week sprints, complete with a Kanban board. Recorded on April 29, 2020. See the original event page for resources for further learning or watch recordings of past events . O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.
Online resource; Title from title screen (viewed April 30, 2020)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos